Influence of the Multifunctional Biological Product Phytop 26.82 on the Growth and Development of Seed Potatoes - Vladislava Maslennikova; Vera Tsvetkova; Andrey Petrov; Rinat Galeev; Maxim Shulga; Natalia Gavrilets; Sergey Ryumkin; Anastasia Shulga; Evgeniy Ryadskiy; Kristina Koloshina; Inga Ryumkina (International Journal of Agronomy)
The study aimed to test a multifunctional technology for potatoes’ biological protection using Phytop 26.82 against black scurf (Rhizoctonia solani Kuhn) and Colorado potato beetle in Western Siberia. The experiment was conducted with the medium-maturing variety “Kemerovchanin.” The product tested was Phytop 26.82. The research methodology was carried out both in laboratory conditions and in the field. In the laboratory, the biological product was used on potato leaves and Colorado potato beetle larvae. The authors revealed the degree of influence of the natural effect Phytop 26.82 on the Colorado potato beetle’s larvae of different ages. The larvae were counted on the 5th, 7th, and 10th days of the experiment. In the field, the authors also revealed the level of the immunogenic effect of the bioagent Phytop 26.82 on the Rhizoctonia stem canker (Rhizoctonia solani Kuhn). The morphological parameters of the Kemerovchanin potato variety were observed during the course of this study. The results of the study showed that the microbial mixture Phytop 26.82 made it possible to increase the biomass of plants by 1.5–1.8 times due to an increase in the length of the aerial part (by 10%), the number of stems (1.2–1.7 times), and the number of stolons (1.5–1.6 times) compared to control. Under the bioagent, Phytop 26.82, Rhizoctonia stem canker on the stems decreased by 45% overall counting weeks. The effectiveness of the bioagent Phytop 26.82 reached 100% in two aspects. One of them was the effectiveness of a biological product in the Colorado potato beetle’s obliteration (Leptinotarsa decemlineata). The second direction of significance was the fight against the black scurf. The use of a mixture of bioagents of the Phytop 26.82 preparation can simultaneously have an insecticidal, fungicidal, and growth-stimulating effect on potatoes.